1992
DOI: 10.1159/000236216
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Analysis of Aztreonam by Antiaztreonam Monoclonal Antibodies and Possible Consequences in Beta-Lactams Hypersensitivity

Abstract: Three cell lines producing monoclonal antibodies, Az-1 (IgG1), Az-2 (IgG1) and Az-3 (IgM) against aztreonam were established. The epitopes and the cross-reactions of the antibodies with various beta-lactams, which were conjugated with human serum albumin (HSA), were examined by enzyme-linked immunosorbent assay (ELISA) and ELISA inhibition test. In ELISA, Az-1 and Az-2 reacted only with aztreonam and ceftazidime, which have the same acyl side chain. Furthermore, Az-2 showed a strong cross-reaction with carumon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Carbapenems are able to induce the formation of specific IgG antibodies in animal models and specific IgE in exposed subjects, leading to allergic reactions [11]. Furthermore, aztreonam has been proven to be immunogenic, inducing IgG antibodies [12], and studies using monoclonal antibodies [20] revealed the importance of the side chain as they could recognize aztreonam and ceftazidime. Considering CLV, initial studies indicated a very low immunogenicity [11], although in the last decade, selective IgE-mediated reactions to this compound have been reported by BAT [21, 22••].…”
Section: Bl Immunological Recognitionmentioning
confidence: 99%
“…Carbapenems are able to induce the formation of specific IgG antibodies in animal models and specific IgE in exposed subjects, leading to allergic reactions [11]. Furthermore, aztreonam has been proven to be immunogenic, inducing IgG antibodies [12], and studies using monoclonal antibodies [20] revealed the importance of the side chain as they could recognize aztreonam and ceftazidime. Considering CLV, initial studies indicated a very low immunogenicity [11], although in the last decade, selective IgE-mediated reactions to this compound have been reported by BAT [21, 22••].…”
Section: Bl Immunological Recognitionmentioning
confidence: 99%
“…These have been recognized by IgG antibodies [58,59]. Three cell lines of hybridoma have been established to AZT [60]. Two of these lines recognize AZT and ceftazidime, indicating that the same acyl side chain is a relevant part of the epitope.…”
Section: Aztreonam (Azt) Is a Monocyclic Bl Isolated Frommentioning
confidence: 99%
“…Así, se han identificado tres epítopos diferentes, la cadena lateral, el núcleo del antibiótico, y la estructura completa. 58 No obstante, al tratarse de fármacos poco utilizados en el tratamiento de infecciones bacterianas, hay pocos estudios sobre la generación de otros determinantes antigénicos tras su degradación y metabolismo.…”
Section: • Cefalosporinasunclassified